Analysis of the Implementation Strategy forElectronification of Local Government Transactions (ETPD) in Soppeng Regency, Indonesia - Andi Ulil Amri Burhan; Gunadi Gunadi (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2023)
Abstract This study aims to determine the appropriate strategy for the implementation of Electronification of Local Government Transactions (ETPD) program in Indonesia through SWOT (strengths, weaknesses, opportunities, and threats) analysis. ETPD program, as promoted by the Presidential Decree Number 3 of 2021, is intended to provide maximum benefits to local government and the community. To achieve the primary objective of this study, a descriptive method was employed, with Soppeng Regency Local Government serving as the focal point. Accordingly, the analysis was based on the Cartesian diagram and from the obtained results it was found that the appropriate strategy for digitalization in the Regency lied in Quadrant II (positive, negative). Thisstudy concluded that internal factors such as the decree regarding the P2DD Task Force, increased regional revenue, young and active employees, and the successful bureaucratic reform initiatives, are significant strengths possessed by theSoppeng Regency Local Government. However, these strengths were accompanied by challenges or threats from certain external factors including insufficient banking infrastructure, lack of digital literacy socialization, and inadequate telecommunications network. Given these conditions, it was crucial to adopt a diversified approach and formulate additional tactical strategy, rather than solely relying on existing ones, to ensure that the local government would be able to effectively carry out their tasks and provide optimal services to the community.